Open Schooling in the Netherlands - Howaard, Jay; Mataheru, Rob (Open Schools Journal for Open Science, 2019)
Here in the Netherlands the main idea about education has been to lock students up in schools and feed them with a lot of information. This has proven to be good method for achieving good exam results, however, students are lacking experience with society. That is why more and more schools are trying to become an open school – a school which seeks connection with the society. There are a lot of ways for schools to interact with society, in this case we will be looking at how two schools, one primary (De Verwondering in Monnickendam) and one secondary (Pieter Groen College in Katwijk), do just that.